2017
DOI: 10.1016/j.brainres.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating functional differences between cortical gyri and sulci via sparse representation HCP grayordinate fMRI data

Abstract: The highly convoluted cerebral cortex is characterized by two different topographic structures: convex gyri and concave sulci. Increasing studies have demonstrated that cortical gyri and sulci exhibit different structural connectivity patterns. Inspired by the intrinsic structural differences between gyri and sulci, in this paper, we present a data-driven framework based on sparse representation of fMRI data for functional network inferences, then examine the interactions within and across gyral and sulcal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In our previous works (Figure S7 and Table S3), it has been demonstrated that 3-hinges have thicker cortices (Li et al, 2015), higher fiber density and diversities (Li et al 2010; Chen et al 2014; Yu et al 2013; Li et al 2017; Ge et al 2017), and are more strongly functionally connected (Jiang et al 2015; Jiang et al 2016a; Jiang et al 2016b; Liu et al 2017) compared to other gyral regions. From the perspective of brain development, we found in our previous works that the 3-hinges with complicated morphology tend to have more diverse connected fibers’ end orientations.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our previous works (Figure S7 and Table S3), it has been demonstrated that 3-hinges have thicker cortices (Li et al, 2015), higher fiber density and diversities (Li et al 2010; Chen et al 2014; Yu et al 2013; Li et al 2017; Ge et al 2017), and are more strongly functionally connected (Jiang et al 2015; Jiang et al 2016a; Jiang et al 2016b; Liu et al 2017) compared to other gyral regions. From the perspective of brain development, we found in our previous works that the 3-hinges with complicated morphology tend to have more diverse connected fibers’ end orientations.…”
Section: Introductionmentioning
confidence: 82%
“…In fact, 3-hinges are of unique structural and functional importance in terms of structural and functional features, brain development and brain evolution, and has the potential to determine inter-subject correspondence (Li, et al 2010; Nie et al 2011; Li, et al, 2015; Chen et al 2012; Chen et al 2014; Zhang et al 2014; Yu et al 2013; Li et al, 2017; Jiang et al, 2015; Jiang et al, 2016a; Jiang et al, 2016b; Ge et al, 2017; Liu et al, 2017). In our previous works (Figure S7 and Table S3), it has been demonstrated that 3-hinges have thicker cortices (Li et al, 2015), higher fiber density and diversities (Li et al 2010; Chen et al 2014; Yu et al 2013; Li et al 2017; Ge et al 2017), and are more strongly functionally connected (Jiang et al 2015; Jiang et al 2016a; Jiang et al 2016b; Liu et al 2017) compared to other gyral regions.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to advanced neuroimaging techniques, such as diffusion tensor imaging (DTI) and functional magnetic resonance imaging (fMRI), we can observe the structural and functional profiles of cortical gyri and sulci in unprecedented details in vivo. A growing number of studies show differences in gyral and sulcal regions, including structural and functional connectivity patterns [7,[18][19][20][21]. For example, neuroimaging and bioimaging studies revealed that DTI-derived streamline fiber terminations mainly concentrate on gyri [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neuroimaging and bioimaging studies revealed that DTI-derived streamline fiber terminations mainly concentrate on gyri [21,22]. Other studies have also made efforts to study the difference between gyri and sulci from the functional perspective [18,20,23,24]. In [18], author demonstrated that the functional connectivity is strong among gyri, weak among sulci, and moderate between gyri and sulci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation